2011
DOI: 10.4238/vol10-3gmr1343
|View full text |Cite
|
Sign up to set email alerts
|

A new single-nucleotide mutation (rs362719) of the reelin (RELN) gene associated with schizophrenia in female Chinese Han

et al.

Abstract: ABSTRACT.Reelin is an extracellular signaling protein that plays an important role in the development of the central nervous system. Postmortem studies have shown lower reelin protein levels in the brains of patients with schizophrenia and bipolar disorder compared with controls. Genetic studies have also shown that mutations in the reelin gene (RELN) increase the risk for schizophrenia and bipolar disorder. We evaluated whether an RELN gene variant, rs362719, which has been associated with increased susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Positive associations between RELN and increased risk of schizophrenia have been identified when RELN variants have been combined with those of additional genes (Hall et al 2007) or in gender-specific manner (Ben-David et al 2010; Kuang et al 2011; Li et al 2011; Liu et al 2011; Pisanté et al 2009; Shifman et al 2008). Hall et al (2007) has demonstrated that SNPs of Reelin were associated with schizophrenia when combined with variants for additional genes, including brain-derived neurotrophic factor, neuropeptide Y, neuregulin 1, and synapsin 3, but not alone (Hall et al 2007).…”
Section: The Role Of Reelin In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Positive associations between RELN and increased risk of schizophrenia have been identified when RELN variants have been combined with those of additional genes (Hall et al 2007) or in gender-specific manner (Ben-David et al 2010; Kuang et al 2011; Li et al 2011; Liu et al 2011; Pisanté et al 2009; Shifman et al 2008). Hall et al (2007) has demonstrated that SNPs of Reelin were associated with schizophrenia when combined with variants for additional genes, including brain-derived neurotrophic factor, neuropeptide Y, neuregulin 1, and synapsin 3, but not alone (Hall et al 2007).…”
Section: The Role Of Reelin In Schizophreniamentioning
confidence: 99%
“…Hall et al (2007) has demonstrated that SNPs of Reelin were associated with schizophrenia when combined with variants for additional genes, including brain-derived neurotrophic factor, neuropeptide Y, neuregulin 1, and synapsin 3, but not alone (Hall et al 2007). Variants of RELN have been associated with increased risk of schizophrenia for women (Ben-David et al 2010; Kuang et al 2011; Li et al 2011; Liu et al 2011; Pisanté et al 2009; Shifman et al 2008). Shifman et al (2008) found that the RELN SNP rs7341475 was associated with increased risk of schizophrenia among Ashkenazi Jewish women.…”
Section: The Role Of Reelin In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…RELN is the most studied schizophrenia candidate gene and the findings show that RELN plays a role in disease etiology [29]. A significant relationship of rs7341475 SNP and rs362719 in female schizophrenia patients [30,31] and rs12705169 in male schizophrenia patients has been indicated [32]. RELN promoter region hypermethylation and RELN selective downregulation have been detected in postmortem schizophrenic brains [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this gene variant was associated with working memory, episodic memory, and executive functioning in the nuclear families of one member with SCZ [21]. Subsequently, a growing number of studies have reported that a number of single nucleotide polymorphisms (SNPs) in the RELN gene were associated with the pathogenesis and/or severity of clinical symptoms of SCZ [22][23][24][25][26][27][28][29]. Hence, based on the low level of RELN in SCZ patients and the relationship between its genetic variation and SCZ, RELN may play a pathogenic role in SCZ [30].…”
Section: Introductionmentioning
confidence: 99%